PEMILIHAN KOMPOSISI VARIASI BASIS FORMULA SEDIAAN SERUM EKSTRAK DAUN KELOR (Moringa oleifera L.) DARI TINJAUAN FORMULA DAN KENYAMANAN PEMAKAIAN - Indriastuti, Marlina; Puspita, Erna (Jurnal Insan Farmasi Indonesia, 2024)
Moringa plants (Moringa oleifera L.) are herbal plants that are used as food and alternative medicine because they have nutrients and potential as medicinal plants. Moringa leaves (Moringa oleifera L.) have antioxidant compounds, so it can be developed into one of the cosmetic preparations. This study aims to determine the formulation and physical evaluation of serum from moringa leaves using a variety of bases. Formulas were made into 3, namely formula 1 HPMC 3%, Carbopol 940 1.5%, and CMC Na 3.5%. Formulation 2 HPMC 2.5%, Carbopol 940 1%, and CMC Na 3%. Formulation 3 HPMC 2%, Carbopol 940 0.5%, and CMC Na 3%. The results showed that formula 3 fulfilled the physical evaluation of serum preparations in the pH test, viscosity test and adhesion test as indicated by the p-value (>0.05). The statistical results of the hedonic test based on color and odor obtained a p-value (>0.05) and the results of the Univariate General Linear Model analysis showed that formula 3 had the highest value of 3.28 on color and 2.16 on odor.